EVALUASI EFISIENSI PENYELENGGARAAN PENDIDIKAN SEKOLAH DASAR DAN MADRASAH IBTIDAIYAH DI KALIMANTAN TIMUR - to, Surip (Jurnal Borneo Administrator, 2011)
Education is the right of every citizen. East Kalimantan Province has a 12-year free education program. Gross enrollment ratios Primary School level in 2009 reached 112.30 percent and high school level GER ranked fourth nationally. On the other hand, East Kalimantan Province also has limitations in education facilities and infrastructure. Some barriers are factors such as land area, population distribution is uneven and limited transportation infrastructure. With these achievements and constraints, it is necessary to evaluate the education in East Kalimantan province. Furthermore, in conducting the evaluation used data analysis tools Envelopment Analysis (DEA) model of Banker Charnes and Cooper (BCC) with output orientation. Results Analysis showed that District/Municipality covers a relatively efficient Paser District, Berau District, Manilau District, Balikpapan Municipality, Samarinda Municipality Penajam Paser District, Tarakan Municipality, East Kutai District, West Kutai District, and Bontang Municipality. While the relatively inefficient covering Kutai Kartanegara District, Bulungan District, Nunukan District, District/Municipality that became a reference in the increased efficiency is Paser District, Berau District, Samarinda and Bontang Municipalities. Furthermore, the Municipality of Samarinda is the most efficient evaluation unit and at most be a reference to increased efficiency.Keywords : evaluation, education, eficiency, and East Kalimantan.Pendidikan adalah hak setiap warga Negara. Provinsi Kalimantan Timur (Kaltim) telah memiliki program pendidikan gratis 12 tahun. Angka Partisipasi Kasar (AKP) jenjang Sekolah Dasar (SD) pada tahun 2009 mencapai 112,30 persen dan APK jenjang Sekolah Menengah Atas (SMA) Kaltim menempati urutan ke-empat nasional. Disisi lain, Provinsi Kaltim  juga menghadapi kendala keterbatas dalam sarana dan prasarana pendidikan. Kendala tersebut disebabkan beberapa faktor antara lain luasnya wilayah, penyebaran penduduk yang tidak merata dan terbatasnya prasarana trasportasi. Dengan prestasi dan Kendala tersebut, maka perlu dilakukan evaluasi  penyelenggaraan pendidikan di Provinsi Kaltim? Selanjuntya, dalam melakukan evaluasi digunakan alat analisis Data Envelopment Analysis (DEA) model Banker, Charnes, dan Cooper (BCC) dengan orientasi output. Hasil Analisis menunjukan bahwa kabupten/kota yang relatif efisien meliputi Kabupaten Paser, Kabupaten Berau, Kabupaten Manilau, Kota Balikpapan, Kota Samarinda, Kabupaten Kutai Barat, Kabupaten Kutai Timur, Kabupaten Penajam Paser  Utara, Kota Tarakan. dan Kota Bontang. Sedangkan yang relatif belum efisien meliputi Kabupaten Kutai Kartanegara, Kabupaten Bulungan, Kabupaten Nunukan, Kabupten/kota yang menjadi referensi dalam peningkatan efisiensi adalah Kabupaten Paser, Kabupaten Berau, Kota Bontang dan Kota Samarinda. Selanjuntya, Kota Samarinda merupakan unit evaluasi yang paling efisien dan paling banyak menjadi referensi peningkatan efisiensi.Kata kunci: evaluasi, pendidikan, efisien dan Kaltim